Comparison of 1-Site and 2-Site Phacotrabeculectomy in the Small Adult Eyes With Concomitant Cataract and Glaucoma. Issue 5 (February 2016) - Xia, Xiaobo; Tian, Ying; Wu, Zhenkai; Wen, Dan; Song, Weitao
Abstract : Abstract: The aim of this study was to compare the outcomes after phacotrabeculectomy at 1 or 2 sites in the small adult eyes with concomitant cataract and glaucoma. Patients who had 1-site (n = 26) or 2-site (n = 14) phacotrabeculectomy over a 4-year period at an eye surgery center were included. Eighteen eyes of 18 patients with glaucoma using any 1 prostaglandin analogue (latanoprost, travoprost, or bimatoprost) were compared with 8 normal control patients. The records of patients were reviewed, and intraocular pressure, best-corrected visual acuity, axial length, anterior chamber depth, corneal endothelial cell (CEC) density, Diopter were measured. The outcome was compared with postoperative and preoperative measurements for 3-month follow-ups. The follow-up time was 3 months. There was no difference between the operations in improving best-corrected visual acuity, lowering intraocular pressure, shortening axial length, and deepening anterior chamber depth. However, 2-site surgery was associated with significantly more CEC loss and refractive error. Postoperative complications were not different between the 2 groups. The CEC loss and the refractive error in 2-site group were higher than that of 1-site group. One-site surgery seems to cause less CEC damage and refractive error than the 2-site operation during the follow-up time of 3 months.